Setting the international research agenda for sarcomas with patients and carers: results of phase II of the Sarcoma Patient Advocacy Global Network (SPAGN) priority setting partnership - Roets, Evelyne; Schuster, K.; Bickley, S.; Wartenberg, M.; Gonzato, O.; Fernandez, N.; Kasper, Bernd; Pilgermann, K.; Wilson, R.; Steeghs, N.; van der Graaf, W. T. A.; van Oortmerssen, G.; et al. (BMC cancer, 2024)
Typically, researchers and clinicians determine the agenda in sarcoma research. However, patient involvement can have a meaningful impact on research. Therefore, the Patient-Powered Research Network (PPRN) of the Sarcoma Patient Advocacy Global Network (SPAGN) set up a Priority Setting Partnership (PSP). The primary objective of this partnership is to identify priorities for research and patient advocacy topics. In the first phase of this PSP, including 264 sarcoma patients and carers from all over the world, 23 research topics regarding sarcomas and 15 patient advocacy topics were identified using an online survey. In the second phase, participants were asked to fill in a top five and a top three of research and patient advocacy topics, respectively. Additionally, sociodemographic characteristics and sarcoma characteristics were collected. Social media channels, local national patient advocacy groups and the SPAGN website were used to distribute the survey. In total, 671 patients (75%) and carers (25%) participated in this survey. The five highest ranked research topics were related to causes of sarcoma (43%), prognosis and risk of recurrence (40%), specific subtypes of sarcoma (33%), the role of immunotherapy, targeted therapy and combined therapy (30%), and hereditary aspects (30%). The three highest ranked patient advocacy topics were improving the diagnostic process of sarcoma (39%), access to tumor DNA analysis (37%) and establishing an international sarcoma registry (37%). This sarcoma PSP has identified priorities for research and patient advocacy, offering guidance for researchers, assisting funding agencies with assessing project relevance and empowering patient advocates to represent the needs of patients and carers.